The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1177/0265407503020003002
|View full text |Cite
|
Sign up to set email alerts
|

What's in a Story? The Relationship Between Narrative Completeness and Adjustment to Relationship Dissolution

Abstract: The construction of narratives has been shown to assist sufferers of emotional or traumatic events -such as the ending of relationships -in making sense of and coming to terms with the event. Despite this connection, few studies have explored how the completeness of the narratives contributes to positive outcomes. Building on research in both communication and psychology, we conceptualized a complete narrative as one that clearly and extensively (1) segmented the experience episodically/sequentially, (2) repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
39
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 18 publications
2
39
1
1
Order By: Relevance
“…This latter trend suggests that the pleasantness of the interaction was central to understanding the quality of family interactions. Previous research identified perspective-taking (Koenig Kellas & Manusov, 2003;Koenig Kellas, 2005) and coherence (Trees & Koenig Kellas, 2009) as particularly important predictors of family satisfaction and functioning. Although these findings support these interactional storytelling behaviors' impact on family well-being, the current findings suggest that-in regard to family members' feelings about the interaction-these interactional storytelling behaviors matter less to individual family members' feelings about the interaction than does engagement or the extent to which the family is warm, involved, lively, and tells the story with positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…This latter trend suggests that the pleasantness of the interaction was central to understanding the quality of family interactions. Previous research identified perspective-taking (Koenig Kellas & Manusov, 2003;Koenig Kellas, 2005) and coherence (Trees & Koenig Kellas, 2009) as particularly important predictors of family satisfaction and functioning. Although these findings support these interactional storytelling behaviors' impact on family well-being, the current findings suggest that-in regard to family members' feelings about the interaction-these interactional storytelling behaviors matter less to individual family members' feelings about the interaction than does engagement or the extent to which the family is warm, involved, lively, and tells the story with positive affect.…”
Section: Discussionmentioning
confidence: 99%
“…These case constructs on the nature of narrative are similar to those proposed by Kellas and Manusov ( 2003). For example in the cases, the narrative broke up the value creation processes by explaining sequences in each sub process, by discussing major events in companies and markets, and by explaining how these and corporate actions created cost, income and value consequences.…”
Section: The Disclosure Content Function Of the Value Creation Storymentioning
confidence: 94%
“…Kellas and Manusov ( 2003) in the context of narrative about personal relationships, conceptualise a complete narrative as one that clearly and extensively (1) segmented the experience episodically/sequentially (2) represented causes and consequences in the explained event (3) developed characters relative to the story (4) evoked and made sense of affect (5) drew meaning from events in the narrative (6) provided a coherent narrative, and (7) attributed responsibility to the characters in the story. These were similar to case constructs in this study concerning the nature of narrative for value creation.…”
Section: Proposed New Measures For Contextual Information Content Of mentioning
confidence: 99%
See 2 more Smart Citations